Peran Bromhexine dalam Tata Laksana Gangguan Pernapasan: Mekanisme dan Efektivitas Klinis - Fariz Nurwidya (MEDICINUS, 2025)
Bromhexine hydrochloride is a mucoactive agent that has been used for more than five decades. Although primarily known as a mucolytic agent, recent evidence indicates a more complex mechanism of action as well as broader potentialtherapeutic applications. This literature review aims to synthesize the latest scientific evidence regarding the mechanism of action, clinical efficacy, and safety of bromhexine in the management of various respiratory tract diseases. A literaturesearch was conducted using the PubMed and Scopus databases with the keywords “bromhexine”, “bromhexin”, “mucolytic”, “COPD”, “bronchitis”, “respiratory tract infection”, and “COVID-19”. Selected articles included clinical trials,in vitro/in vivo studies, reviews, and metaanalysis published up to 2025. The review found that bromhexine acts through several mechanisms, including mucin depolymerisation via disulfide bonds cleavage, stimulation of alveolar type II cellssurfactant production, enhancement of ciliary system activity, as well as anti-inflammatory and antioxidant activities. Bromhexine has demonstrated effectiveness as an adjuvant therapy in acute and chronic bronchitis, chronic obstructivepulmonary disease (COPD), asthma, and bronchiectasis, by reducing sputum viscosity and improving productive cough symptoms. In conclusion, bromhexine shows good efficacy and safety for the management of mucus production and transport disorders in various pulmonary diseases, owing to its mucolytic and surfactant-stimulating properties. These mechanisms remain relevant in the modern era of respiratory disease management.